The Impact of Residual Subgingival Cement on Biological Complications Around Dental Implants: A Systematic Review. Issue 3 (June 2017) - Quaranta, Alessandro; Lim, Zhuo Wei; Tang, Joyce; Perrotti, Vittoria; Leichter, Jonathan
Abstract : Objectives: To perform a systematic review on the impact of residual subgingival cement on peri-implant diseases and crestal bone loss. Material and Methods: MEDLINE, SCOPUS, ISI Web of Knowledge and Cochrane Central Register of Controlled Trials (CENTRAL) databases were used to identify articles published without time limits. Results: A total of 6 articles were selected for a total of 389 patients (687 implants). The studies were heterogeneous and had a moderate-to-high risk of bias, but met the inclusion criteria. Four of 6 studies were published by the same research group and assessed similar populations over time. A positive relationship between residual cement and peri-implant inflammation was observed. Data on peri-implant probing depths and crestal bone loss were reported in 1 study. Conclusion: Residual subgingival cement seems to be strongly associated with peri-implant mucositis which is a risk factor for increased probing depths crestal bone loss and peri-implantitis. Zinc oxide eugenol cements should be preferred to resin cements especially in patients with a history of periodontitis.